2021
DOI: 10.1177/13558196211029323
|View full text |Cite
|
Sign up to set email alerts
|

Getting the whole story: Integrating patient complaints and staff reports of unsafe care

Abstract: Objective It is increasingly recognized that patient safety requires heterogeneous insights from a range of stakeholders, yet incident reporting systems in health care still primarily rely on staff perspectives. This paper examines the potential of combining insights from patient complaints and staff incident reports for a more comprehensive understanding of the causes and severity of harm. Methods Using five years of patient complaints and staff incident reporting data at a large multi-site hospital in London… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 24 publications
3
28
0
1
Order By: Relevance
“…This finding echoes previous work demonstrating that patients frequently report issues around ‘unsafe care’ that healthcare professionals would consider to be inconsequential 19. Patient-reported safety concerns include physical discomfort (eg, noise, light, food), lack of security (including fear of other patients), uncertainty (eg, about discharge), process failures (delays or omissions) and patient–provider interactions (eg, poor communication/lack of compassion) 8 19–21…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…This finding echoes previous work demonstrating that patients frequently report issues around ‘unsafe care’ that healthcare professionals would consider to be inconsequential 19. Patient-reported safety concerns include physical discomfort (eg, noise, light, food), lack of security (including fear of other patients), uncertainty (eg, about discharge), process failures (delays or omissions) and patient–provider interactions (eg, poor communication/lack of compassion) 8 19–21…”
Section: Introductionsupporting
confidence: 75%
“…Our study indicates that patients monitor certain aspects of hospital care, including staff undertaking clinical procedures and observing organisational-level processes, such as cleaning. The findings of this study and others demonstrate that, through their observations, patients provide valuable insights into safety that could complement existing patient safety measurements 8 21. Importantly, our study highlights that patients do not necessarily express safety concerns using the language of the clinical risk paradigm.…”
Section: Discussionmentioning
confidence: 53%
“…This is because patient complaints can provide important and additional information to healthcare delivery on how to improve patient safety and comfort, hence should be given the appropriate response in order to make them comfortable. This is in agreement with a study conducted in the United Kingdom among 446 nurses where participants indicated that they reported patients’ complaints about prompt feedback [ 32 ]. In reporting patients’ complaints, nurses indicated that the right procedure should be followed in order to prevent conflict between patients and the staff involved.…”
Section: Discussionsupporting
confidence: 92%
“…Considering that each complaint is considered as a valuable opportunity to find a way to improve the quality of service that patients receive, it can be done by combining heterogeneous data from different perspectives, including by integrating patient complaints and incident report data. Staff achieved a more comprehensive analysis of critical safety incidents (8).…”
Section: Introductionmentioning
confidence: 99%